Dan in real life - Shestack, Jonathan; Epstein, Brad.; Gardner, Pierce; Hedges, Peter; Carell, Steve, 1963-; Binoche, Juliette, 1964-; Cook, Dane.; Mahoney, John, 1940-; Blunt, Emily; Wiest, Dianne; Touchstone Pictures; Focus Features; et al. (Burbank, CA : Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2008)
Dan Burns is a local newspaper advice columnist. He has three daughters and is a widower. He brings the family to his parent's house for a family gathering. Dan goes to a local bookstore, he meets Marie, but when he gets home, he finds out that Marie is actually dating his brother Mitch. Dan's mother Nana announces that she met an old acquaintance of Dan's, Ruthie Draper and that she has set up a date between Dan and Ruthie. Dan refuses to go. Mitch suggests that they could make it a double date and Dan agrees. Ruthie turns out to be very hot, but Dan isn't really interested in her. When Marie indicates that Ruthie is not right for him, Dan feigns interest and starts dancing with Ruthie. Marie gets jealous and joins the floor with Mitch, leading to an upstaging contest between Dan and Marie.
DVD, region 1, widescreen (1.85:1, enhanced) presentation; Dolby Digital 5.1 surround, digitally mastered.
English, French or Spanish dialogue, French or Spanish subtitles; closed-captioned.
Title from container.
Steve Carell, Juliette Binoche, Dane Cook, John Mahoney, Emily Blunt, Dianne Wiest.
Director of photography, Lawrence Sher ; editor, Sarah Flack ; music, Sondre Lerche ; costume designer, Alix Friedberg ; production designer, Sarah Knowles.
Originally released as a motion picture in 2007.
Keywords: Widowers -- United States -- Drama; Man-woman relationships -- United States -- Drama; Dating (Social customs) -- United States -- Drama; Feature films; Romantic comedy films; Films for the hearing impaired